2023
DOI: 10.1186/s13065-023-00917-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, DFT investigations, antioxidant, antibacterial activity and SAR-study of novel thiophene-2-carboxamide derivatives

Abstract: Synthetic strategy for the synthesis of thiophene 2-carboxamide derivatives substituted with hydroxyl, methyl and amino groups at position-3 was proposed. The strategy includes the cyclization of the precursor ethyl 2-arylazo-3-mercapto-3-(phenylamino)acrylate derivatives, 2-acetyl-2-arylazo-thioacetanilide derivatives and N-aryl-2-cyano-3-mercapto-3-(phenylamino)acrylamide derivatives with N-(4-acetylphenyl)-2-chloroacetamide in alcoholic sodium ethoxide. IR, 1H NMR, and mass spectroscopic analyses were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 69 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…The most recent research of Metwally et al [ 50 ] indicated that thiophene-2-carboxamide ( Figure 7 ) derivatives showed antibacterial properties, with S. aureus , B. subtilis , E. coli , and P. aeruginosa being the most susceptible to the activity of the tested compounds. While the results showed no indication of targeting virulence factors, the very fact that the novel synthesized compounds possessed microbicidal activity with no targeted virulence factors whatsoever suggests that there is still hope for old-fashioned drugs as antimicrobials.…”
Section: Thiophenesmentioning
confidence: 99%
“…The most recent research of Metwally et al [ 50 ] indicated that thiophene-2-carboxamide ( Figure 7 ) derivatives showed antibacterial properties, with S. aureus , B. subtilis , E. coli , and P. aeruginosa being the most susceptible to the activity of the tested compounds. While the results showed no indication of targeting virulence factors, the very fact that the novel synthesized compounds possessed microbicidal activity with no targeted virulence factors whatsoever suggests that there is still hope for old-fashioned drugs as antimicrobials.…”
Section: Thiophenesmentioning
confidence: 99%
“…Several studies have been carried out using various sulfur and/ or nitrogen-containing heterocyclic compounds, including thiophene, thiazole, and pyridine, directed towards different pathologies. These thiophene, thiazole, and pyridine-containing compounds show anticancer [4][5][6][7][8], anti-inflammatory [9][10][11], antibacterial [12][13][14], antioxidant [15], anti-oxidant [16], anti-fungal [17,18], anti-coronavirus [19,20] properties. Thiazoles were also found to act as anti-Alzheimer [21], anti-tubercular [22], and anti-diabetic [23].…”
Section: Introductionmentioning
confidence: 99%
“…When compared to oxygen, nitrogen and sulphur, its electronegativity is lower, which means it interacts favourably with enzymes and receptors inside microorganisms [9,10]. Through its chelating qualities, which enable it to form coordination complexes with metal ions, the sulfur atom can interfere with metal-dependent enzymes that are necessary for microbial growth and metabolism [11,12].…”
Section: Introductionmentioning
confidence: 99%